2007
DOI: 10.1002/jmri.20889
|View full text |Cite
|
Sign up to set email alerts
|

Parallel imaging technique for the external carotid artery and its branches: Comparison of balanced turbo field echo, phase contrast, and time‐of‐flight sequences

Abstract: Purpose:To evaluate the parallel imaging technique in the external carotid artery and its branches using 3D balanced turbo field echo (3D bTFE), 3D phase-contrast (3D PC), and 3D time-of-flight (3D TOF) MR angiography (MRA) sequences. Materials and Methods:A total of 26 healthy volunteer subjects underwent 3D bTFE, 3D PC, and 3D TOF MRA with the parallel imaging sensitivity encoding (SENSE) technique. The obtained images were read in a blinded fashion by three radiologists. Interreader and intersequence statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…Second, balanced SSFP MRA with a Time-SLIP was not compared with PC MRA. Sumi et al (6) reported that PC with the parallel imaging performed the best for overall visibility of the ECA system among TOF, PC, and balanced SSFP, although arterial spin-labeling method was not used in their study. We did not assess PC MRA because the parallel imaging was not available for PC sequence in the MR scanner used in this study.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Second, balanced SSFP MRA with a Time-SLIP was not compared with PC MRA. Sumi et al (6) reported that PC with the parallel imaging performed the best for overall visibility of the ECA system among TOF, PC, and balanced SSFP, although arterial spin-labeling method was not used in their study. We did not assess PC MRA because the parallel imaging was not available for PC sequence in the MR scanner used in this study.…”
Section: Discussionmentioning
confidence: 94%
“…A strong contrast between the blood vessels and muscle can be obtained, but veins and salivary gland ducts as well as arteries show high signal intensity. Sumi et al (6) stated that an effective method of separating arteries from veins and salivary gland ducts was needed for balanced SSFP MRA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations